5g+8=6g+4

Simple and best practice solution for 5g+8=6g+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5g+8=6g+4 equation:


Simplifying
5g + 8 = 6g + 4

Reorder the terms:
8 + 5g = 6g + 4

Reorder the terms:
8 + 5g = 4 + 6g

Solving
8 + 5g = 4 + 6g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-6g' to each side of the equation.
8 + 5g + -6g = 4 + 6g + -6g

Combine like terms: 5g + -6g = -1g
8 + -1g = 4 + 6g + -6g

Combine like terms: 6g + -6g = 0
8 + -1g = 4 + 0
8 + -1g = 4

Add '-8' to each side of the equation.
8 + -8 + -1g = 4 + -8

Combine like terms: 8 + -8 = 0
0 + -1g = 4 + -8
-1g = 4 + -8

Combine like terms: 4 + -8 = -4
-1g = -4

Divide each side by '-1'.
g = 4

Simplifying
g = 4

See similar equations:

| c/4=10.5 | | (9)^1/2 | | 13.75x41/2 | | 2y-7+4y-4=-23 | | -0.5q^2+312.5=0 | | 2y+4y-4=-2 | | n/10=361/5 | | 2(4x-16)-5s=-5 | | y/6=-6 | | (19.00/25.00)*100 | | a/0.7=8 | | w(1+2w)=88 | | 3/4x-2y+7=0 | | e/1=12.5 | | 4(x+2)-(2x-5)=0 | | z/2=-9 | | 3m^2+8m^2-3m^2=0 | | X+2+3x-8=90 | | 4n^2+n-37=0 | | c/8=36 | | 4h-1-7h=8-15h+2 | | x^3+9x^2-10x=72 | | 7b^2-6b-4=-3 | | 5b-5-11b-9=0 | | 3(6v-8)=-132 | | 7b^2-6b-4=3 | | b/3=31 | | n-23=15 | | 5a-12=2a | | 8x^2+18x=-7 | | .680(-x)= | | -6(b+7)=-84 |

Equations solver categories